Social consequences of globalization: from isolated to globally connected - Sun, Jiaming (Henry Stewart Talks, 2013)
An unprecedented transformation, "The Middle Kingdom"- Foreign contacts, Foreign civil-related notary, Kinship network to overseas Chinese, Growing attractiveness to foreigners, Foreign students in China, International schools, Sent officials abroad for training, Cross-cultural marriages, An indicator of the openness of a country, Chinese studied abroad, Significant number of returnees, Booming overseas tourism, The Chinese wave, Instantaneous connections worldwide, "Internet Citizen" in China, Valentine's Day in China, Consumption and lifestyle of Chinese, China's rising yuppie, Being nurtured with transnational identities